Study on functional outcome of intra articular fractures of distal humerus managed by locking compression plate - Bhat, Adarsh Krishna; Jacob, Tigy Thomas; Sameul, Shajimon (International Journal of Research in Orthopaedics, 2021)
Background: The primary goal in management of intra articular fractures of distal humerus is to achieve stable and mobile elbow. Type C fracture of distal humerus is a relatively uncommon fracture. Internal fixation is difficult but anatomical reduction is needed to prevent poor functional outcome and degenerative changes. Methods: Functional outcome of patients who underwent open reduction internal fixation with locking compression plates for intra articular fractures of distal humerus at the department of orthopedics, Government medical college Kottayam, from December 2017 to July 2019, were assessed using Mayo elbow performance index. A total of 30 patients were studied. Results: Excellent and good results were found in 25 cases, 3 patients had fair outcome and 2 patients had poor result. Complications encountered in our study were, infection (superficial treated with antibiotics-3 cases), heterotopic ossification (3 cases), hard ware prominence (2 cases) and non-union (1 case). Conclusions: Complications were minimal and outcomes were good in patients with type C distal humerus fractures who underwent bicolumn locking compression plates fixation by posterior approach.